Organocatalytic enantioselective aza-Friedel–Crafts reaction between benzothiazolimines and 2-naphthols for the preparation of chiral 2′-aminobenzothiazolomethyl naphthols. Issue 35 (25th August 2021) - Li, Chen-Yi; Xiang, Min; Zhang, Jian; Li, Wen-Sheng; Zou, Ying; Tian, Fang; Wang, Li-Xin
Abstract : An organocatalytic enantioselective aza-Friedel–Crafts reaction between 2-naphthols and benzothiazolimines has been developed, and a series of chiral 2′-aminobenzothiazolomethyl naphthols have been prepared under mild conditions. Abstract : A bifunctional cinchona squaramide catalyzed enantioselective aza-Friedel–Crafts reaction between 2-naphthols and benzothiazolimines has been developed, and a series of chiral 2′-aminobenzothiazolomethyl naphthols with potential antiproliferative and anthelmintic activities have been successfully and effectively prepared in good to excellent yields (up to 98%) with excellent enantioselectivities (up to >99% ee) even in a scale-up preparation under mild conditions.